Time Difference Between Onsets of Lateral and Medial Hamstring Muscles During Gait in Patients With Patellofemoral Pain: A Preliminary Study - Coşkunsu, Dilber Karagözoğlu; Can, Filiz; Kuchimovs, Shavkat; AKALAN, NAZİF EKİN; Kılıçoğlu, İ. Önder; Öztürk, Necla (Marmara Univ., Inst Health Sciences, 2022)
Objective: Early activation of lateral hamstrings (LH) relative to medial hamstrings (MH) has been thought to be the cause of abnormal knee abduction and external rotation of the tibia, which affects the orientation of patellar tendon and increases lateral patellofemoral compression. Therefore, early activation of LH relative to MH is considered to have a role in the patellofemoral pain (PFP). The aim of this study was to investigate the time difference between MH and LH onsets in patients with PFP during gait. Methods: Thirteen patients with bilateral PFP (mean age 28.73 +/- 7.44 years) and 13 asymptomatic subjects (mean age 30.47 +/- 6.22 years) were recruited in the study. Gait analysis was performed using the ELITE system (BTS, Milano-Italy) with video cameras (TVC, BTS, Milano-Italy). Participants were requested to walk at a self-selected speed on a force platform, and EMG data were recorded from MH and LH muscles for 10 initial contacts by using TELEEMG (BTS, Milano-Italy). Time difference between the onsets of the MH and LH was calculated for each initial contact by using moving averaging method, then their mean was obtained for each participant. Results: The time difference between onsets of MH and LH was - 26.9 +/- 22.2 ms for PFP subjects and - 11.2 +/- 14.2 ms for control subjects, and LH mainly became activated earlier compared to MH in most of the subjects in both groups. There was a statistically significant difference between the time differences of the groups (p=0.041). Conclusion: Our findings suggest that LH displayed an earlier activation in subjects with PFP compared to control subjects during gait.
Keywords: Hamstrings; Surface EMG; Patellofemoral Pain; Gait; Time Difference